Tuber cinereum lipoma - Manappallil, Robin George; VG, Pradeep Kumar; Suresh, Chinganthara Cleetus (Asian Journal of Medical Sciences, 2018)
No abstract Asian Journal of Medical Sciences Vol.9(2) 2018 45-46